Фізичний опір як одна з підстав застосування сили до засуджених: соціально-правовий аспект - Колб, І; Kolb, I (СНУ ім.Лесі Українки, 2019)
У статті з’ясовано соціально-правову природу фізичного опору засуджених, позбавлених волі, у контексті застосування до цих осіб передбачених законом заходів їх приборкання, а також визначена роль і вплив на формування зазначеної протиправної поведінки фонових явищ. Автор вважає, що персоналу ДКВС України в обов’язковому порядку варто враховувати не тільки формально-юридичні, а й фактичні підстави для застосування заходів фізичного впливу, спеціальних засобів для подолання фізичного опору з боку засуджених, включаючи й вплив на правопорушників наявних в кримінальновиконавчій установі фонових явищ. Такий підхід не тільки дозволить на практиці більш предметно реалізовувати принцип гуманізму, а також запобігати вчиненню з боку засуджених більш тяжких суспільно небезпечних діянь. The article deals with the socio-legal nature of the physical resistance of the imprisoned in the context of the application of legal measures to neutralize them. The study highlights the role of the background phenomena and their impact on the formation of the unlawful behavior of the prisoners. The author argues that the staff of the State Criminal Enforcement Service of Ukraine ought to take into account not only formal and legal factors but also the actual grounds for the application of physical influence measures to subdue physical resistance on the part of prisoners including the influence of the background phenomena existing in the penal institution. Such an approach will not only make it possible to put into practice the principle of humanism in a more substantive way, but also prevent more serious socially dangerous acts on the part of prisoners. This practice will allow to humanize the relations of the penitentiary institution staff and the convicted persons, which has always been and remains an urgent problem in the process of execution and serving sentences, and meets the requirements of the Conception of reforming (development) of the penitentiary system of Ukraine approved by the Cabinet of Ministers of Ukraine in September of 2017.
Physical Resistance as One of the Reasons for Using Force against Prisoners: Social and Legal Aspects
Keywords: фізичний опір; правові підстави; фактичні підстави; засуджений; персонал колоній; запобігання; злочин; правопорушення; заходи вгамівного порядку; фонові явища; позбавлення волі; physical resistance; legal grounds; physical grounds; convicted; colony personnel; prophylaxis; the crime; offense; restraining measures; background phenomena; deprivation of liberty; 343.8